GÖRSEL SANATLAR ÖĞRETMEN ADAYLARININ TEKNOLOJİYE İLİŞKİN METAFORİK ALGILARI - Ferit KARAKOYUN (International Journal of Eurasia Social Sciences, 2017)
The purpose of the present study was to identify visual arts pre-service teachers’ perceptions of technology via metaphors. The participants of the study were 101 pre-service teachers attending Department of Fine Arts, Painting Department of Education at Ziya Gökalp Education Faculty of Dicle University in the Spring Term of the academic year of 2015-2016. These pre-service teachers were asked to complete the sentence: “Technology is like ……., because it is …….”. Data obtained has been evaluated via content analysis method. Depending on the findings, it could be stated that 92 pre-service teachers developed 57 different metaphors and these metaphors were gathered under 10 categories. Pre-service teachers mostly reported positive views about technology. In addition, Pre-service teachers often used metaphors such as life, information source, convenience and necessity to describe technology.